Effect of dispersed crude oil on cardiac function in seabass Dicentrarchus labrax. (September 2015) - Tissier, Florine; Dussauze, Matthieu; Lefloch, Nina; Theron, Michael; Lemaire, Philippe; Le Floch, Stéphane; Pichavant-Rafini, Karine
Highlights: Dicentrarchus labrax were used in this ecotoxicological study. Fish were exposed to dispersant, mechanical and chemical oil dispersion. Cardiac contraction parameters were impacted in the presence of oil. Cardiac energy metabolism was impacted by dispersant alone. Abstract: In this study, the impact of dispersed oil was assessed in Dicentrarchus labrax, a fish frequently used as an oil contamination indicator species. Fish were exposed for 48 h to (mechanically and chemically) dispersed oil and dispersant alone. The impact of these exposure conditions was assessed on cardiac function by measuring (i) the contraction strength, the contraction and the relaxation speeds (ii) the cardiac energy metabolism using respirometry on permeabilized cardiac fibers. Compared to control, the increase of polycyclic aromatic metabolites observed in the bile indicated oil contamination in our fish. Following 48 h of oil exposure at realistic oil concentrations, alterations of cardiac performances were observed. A decrease in contraction strength, contraction and relaxation speeds was observed in the presence of oil without effect of dispersant on these three parameters. Looking at cardiac energy metabolism, dispersant alone decreases all the activity of the respiratory chain and increases the proton leak. From these results, it appears that the observed decrease in cardiac performance in fish exposed to oil was not linked to a decrease in energy availability.